The Current Role of Metastasis-Directed Therapy for Oligometastatic Renal Cell Carcinoma - Hyung Joon Kim (Journal of Urologic Oncology)
Approximately 20% of newly diagnosed renal cell carcinoma (RCC) cases exhibit synchronous metastases, while 20% to 40% of initially localized RCC cases subsequently develop distant metastases after surgical intervention. In the management of oligometastatic RCC with a restricted number of metastatic sites, metastasis-directed therapy (MDT) plays a crucial role within the multimodal therapeutic framework. MDT, which encompasses surgical metastasectomy and stereotactic body radiation therapy (SBRT), seeks to prolong survival and increase quality of life by offering an interruption of systemic therapy. Research has demonstrated that complete metastasectomy is essential for attaining an optimal survival advantage. The criteria for patient selection remain ambiguous; nonetheless, it is crucial to consider the location of metastases and patient risk stratification. SBRT is demonstrably successful in RCC and is being progressively utilized in oligometastatic RCC. The sequencing of advanced systemic agents with comprehensive local treatment of primary and metastatic sites for oligometastatic RCC has demonstrated potential.